f(x) = 7x² - 3x + 1
g(x) = 3x - 2
1. g(0) This means that x is 0, so you can plug in 0 for x in the equation:
g(x) = 3x - 2
g(0) = 3(0) - 2
g(0) = -2
2. g(1) x is 1
g(x) = 3x - 2
g(1) = 3(1) - 2
g(1) = 3 - 2
g(1) = 1
3. f(1) x is 1
f(x) = 7x²- 3x + 1
f(1) = 7(1)² - 3(1) + 1
f(1) = 7 - 3 + 1
f(1) = 5
4. f(x) = 7x²- 3x + 1
f(-2) = 7(-2)²- 3(-2) + 1
f(-2) = 7(4) + 6 + 1
f(-2) = 28 + 7
f(-2) = 35
First, do the prime factorization.
96 = 2 x 2 x 2 x 2 x 2 x 3
72 = 2 x 2 x 2 x 3 x 3
The GCF is the product of their shared factors.
They share 2, 2, 2, and 3.
2 x 2 x 2 x 3 = 24.
Their GCF is 24.
Answer:
y = 0.5
Step-by-step explanation: